2019
DOI: 10.1038/s41598-019-48070-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Prognosis of Patients With Lupus Nephritis Submitted to Renal Transplantation

Abstract: This stydy aimed to evaluate the epidemiological and clinical profile and outcome of patients with lupus nephritis (LN) submitted to renal transplantation. Retrospective cohort study based on the records of 35 LN patients submitted to renal transplantation at a single center in Brazil between July 1996 and May 2016. The Kaplan-Meier method was used to estimate 6-month, 1-year and 5-year graft survival. The sample included 38 transplantations (3 of which retransplantations). The mean age at the time of SLE diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…38 In this study, death-censored graft survival rates for the first renal transplant were similar to those described by other authors (Table 4). 7,[9][10][11][15][16][17][18][19][22][23][24][27][28][29][30]32 Studies conducted in Latin America, where SLE patients are mostly Mestizos, showed graft survival rates similar to those found in our cohort. Naranjo-Escobar et al, 11 showed similar graft survivals in Colombian patients (92% at one year, and 83% at five years), while in a Mexican study by Ram ırez-Sandoval, et al, 16 a graft survival of 81% was found at five years and 79% at ten years.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…38 In this study, death-censored graft survival rates for the first renal transplant were similar to those described by other authors (Table 4). 7,[9][10][11][15][16][17][18][19][22][23][24][27][28][29][30]32 Studies conducted in Latin America, where SLE patients are mostly Mestizos, showed graft survival rates similar to those found in our cohort. Naranjo-Escobar et al, 11 showed similar graft survivals in Colombian patients (92% at one year, and 83% at five years), while in a Mexican study by Ram ırez-Sandoval, et al, 16 a graft survival of 81% was found at five years and 79% at ten years.…”
Section: Discussionsupporting
confidence: 82%
“…In our population, patient survival rates were lower than those reported in other studies (Table 4). 7,[9][10][11][15][16][17][18][19][22][23][24][27][28][29][30]32 These differences could partially be explained by different times of kidney transplant or recruitment period. In this light, the patient survival rates in our cohort at one, three, and five years after 2005 (93%, 93%, and 85%, respectively) were significantly better than those observed before 2005 (85%, 75%, 74%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before transplantation, it is essential to ensure that SLE is in remission status, and three months period of dialysis is usually advisable. It is well documented that the transplanted kidney in LN patients survives less than the kidney transplanted in patients without LN, and the patient outcome is better with living-related than the cadaveric allografts, although it can be conducted from cadaveric and non-related live donor with reasonable improvement of outcome (86). The reasons for the early graft failure in LN are not clear enough, however, they are probably due to LN reoccurrence and/or concomitant antiphospholipid antibody syndrome (87).…”
Section: Renal Transplantationmentioning
confidence: 99%